2016
DOI: 10.3233/jad-150376
|View full text |Cite
|
Sign up to set email alerts
|

Two Phase 2 Multiple Ascending–Dose Studies of Vanutide Cridificar (ACC-001) and QS-21 Adjuvant in Mild-to-Moderate Alzheimer’s Disease

Abstract: Vanutide cridificar (ACC-001), an immunotherapeutic vaccine, is a potentially disease-modifying therapy that aims to reduce brain amyloid-β (Aβ) plaques in patients with Alzheimer's disease (AD). ACC-001 was evaluated in two phase 2a, multicenter, randomized, third party-unblinded, placebo-controlled, multiple ascending-dose studies of ACC-001 (3μg, 10μg, 30μg) with and without QS-21 adjuvant that enrolled patients with mild-to-moderate AD (n = 245). Patients were treated with up to five doses of study vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 32 publications
2
68
0
Order By: Relevance
“…In addition to ACI-24, these new-generation active vaccines include ACC-001 [51] and CAD-106 [52]. Phase I trials for these approaches showed positive antibody responses with no signs of adverse inflammation [53,54].…”
Section: Alzheimer's Disease In Down Syndromementioning
confidence: 97%
“…In addition to ACI-24, these new-generation active vaccines include ACC-001 [51] and CAD-106 [52]. Phase I trials for these approaches showed positive antibody responses with no signs of adverse inflammation [53,54].…”
Section: Alzheimer's Disease In Down Syndromementioning
confidence: 97%
“…In preclinical studies, it was shown to generate Nterminal Aβ Abs in adult nonhuman primates without inducing Aβ-directed T cell response, supporting further clinical studies. Several phase II trials in patients with mild to moderate AD were conducted in USA, Europe, and Japan by using 3 doses of ACC-001 (3, 10 and 30 μg) with and without the adjuvant QS-21 (50 μg) or placebo to investigate doserange, safety, immunogenicity and long term treatment (Arai et al, 2015;Pasquier et al, 2016). ACC-001+QS-21 elicited high, sustained anti-Aβ IgG Ab titers compared with ACC-001 alone, highlighting the role of QS-21 in this effect.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…To date, none of the treatments available for AD slow or stop neurodegeneration. Clinical trials with Aβ therapies, including immunotherapy, have thus far failed to show any reduction in neurofibrillary pathology or improvement in cognitive performance of patients with AD [510]. …”
Section: Introductionmentioning
confidence: 99%